Echocardiographic assessment of right ventricular function in routine practice: Which parameters are useful to predict one-year outcome in advanced heart failure patients with dilated cardiomyopathy?. Issue 4 (October 2017) - Kawata, Takayuki; Daimon, Masao; Kimura, Koichi; Nakao, Tomoko; Lee, Seitetsu L.; Hirokawa, Megumi; Kato, Tomoko S.; Watanabe, Masafumi; Yatomi, Yutaka; Komuro, Issei
Abstract: Background: Right ventricular (RV) function has recently gained attention as a prognostic predictor of outcome even in patients who have left-sided heart failure. Since several conventional echocardiographic parameters of RV systolic function have been proposed, our aim was to determine if any of these parameters (tricuspid annular plane systolic excursion: TAPSE, tissue Doppler derived systolic tricuspid annular motion velocity: S ′, fractional area change: FAC) are associated with outcome in advanced heart failure patients with dilated cardiomyopathy (DCM). Methods: We retrospectively enrolled 68 DCM patients, who were New York Heart Association (NYHA) Class III or IV and had a left ventricular (LV) ejection fraction <35%. All patients were undergoing evaluation for heart transplantation or management of heart failure. Primary outcomes were defined as LV assist device implantation or cardiac death within one year. Results: Thirty-nine events occurred (5 deaths, 32 LV assist devices implanted). Univariate analysis showed that age, systolic blood pressure, heart rate, NYHA functional class IV, plasma brain natriuretic peptide concentration, intravenous inotrope use, left atrial volume index, and FAC were associated with outcome, whereas TAPSE and S ′ were not. Receiver-operating characteristic curve analysis showed that the optimal FAC cut-off value to identify patients with an event was <26.7% (area under the curve = 0.74). The event-free rate determined by Kaplan–Meier analysis was significantly higher in patients with FAC ≥ 26.7% than in those with FAC < 26.7% (log-lank, p = 0.0003). Moreover, the addition of FAC < 26.7% improved the prognostic utility of a model containing clinical variables and conventional echocardiographic indexes. Conclusions: FAC may provide better prognostic information than TAPSE or S ′ in advanced heart failure patients with DCM.